Overcoming water scarcity and quality constraints: Water, Conflict, and Cooperation - Wolf, Aaron T. (International Food Policy Research Institute, 2001)
River basins and groundwater aquifers that cross international boundaries present increased challenges to effective water management because hydrologic needs are often overwhelmed by political considerations. While the potential for paralyzing disputes is especially high in these transnational basins, the record of violence is actually greater within a nation’s boundaries.